SOME ASPECTS OF THE EATIOLOGY OF PARODONTUS DISEASES. (LITERATURE REVIEW) - N.N. Saveleva; I.I. Sokolova; S.I. German; T.V. Tomilina (Ukrainian Medical Stomatological Academy, 2018)
The review of the scientific literature is devoted to the topical issues of studying the etiology of periodontal diseases, which are one of the most common and complex pathologies of the maxillofacial region. Analysis of recent studies proves a stable relationship between the development of periodontal diseases and disorders in the immune system, the neurohumoral system, metabolic disorders, genetic predisposition, and so on. The article presents the data obtained in the course of studying the literature on the role of disorders in the functioning of individual organs (gastrointestinal tract, liver, lungs, heart, and urinary system) in the development of chronic periodontal diseases. The article notes that the anatomical and physiological proximity of the periodontal and digestive tract tissues, the generality of innervation and humoral regulation create prerequisites for the involvement of periodontal disease in the pathological process in diseases of the gastrointestinal tract. One of the main etiological factors in the development of inflammatory diseases of the gastrointestinal tract and periodontium is Helicobacter pylori, which is found in the loci of the oral cavity: in the oral and gingival fluid, on the mucous membrane of the tongue and cheeks, and in the periodontal pockets. It is pointed out that the liver also occupies a special place in the development of periodontal diseases, which is explained by the performance of its significant functions for the human body: regulatory, metabolic, antitoxic and other. There is evidence that the pathology of periodontal disease plays a leading role in the structure of dental diseases in patients with chronic obstructive pulmonary diseases, which is clinically manifested by symptoms of generalized periodontitis of the І-ІІ degrees of development and its complications - partial or complete secondary adentia, and with tooth preservation - defects in dental series and violations of occlusion, function, aesthetics. Scientists suggest a general biological mechanism for the development of generalized periodontitis and cardiovascular diseases, linking the development of periodontal diseases in patients with cardiovascular pathology with microcirculatory disorders. The dependence of the severity of inflammatory changes in the periodontal tissues on the disturbances of salt metabolism in urolithiasis is proved. The data obtained indicate that diseases of the internal organs contribute to the structural damage of periodontal tissues and they are a risk factor for periodontal diseases, which necessitate the presence of not only theoretical knowledge and practical skills in dentistry, but also their awareness of the features and clinical manifestations of somatic pathology. An urgent and justified step in the treatment of periodontal diseases is also the involvement in the process of rendering complex dental care to internist doctors capable of quickly and qualitatively assessment the condition of the internal organs and the basic systems of the patient's body.